CLUSTER ANALYSIS OF INTEGRATED "DRUG SUPPLY" CONCEPT - G. S. Barkaev; T. I. Kabakova; A. B. Goryachev (Volgograd State Medical University, Pyatigorsk Medical and Pharmaceutical Institute, 2022)
The aim of the article is the structure and content specification of the subject area professional term "drug supply" in order to deepen and concretize the conceptual apparatus in the field of the pharmaceutical activity.Materials and methods. The review presents the analysis of 389 titles of scientific pharmaceutical publications for the periods of 1995-1998 and 2010-2019. The selection of publications was carried out by the random sampling based on the phrases: «drug provision», «medical care», «provision of medicines», «pharmaceutical care», «medicinal services», «drug supply» and their English-language counterparts in Russian and foreign electronic information sources. A methodological base of the study was a cluster analysis of the subject area concept of "drug supply" according to the methodology proposed by E.A. Korzhavykh and I.V. Voronovich. In this study, a cluster was interpreted as a set of publications in which a certain pair of terms was simultaneously cited with a preset frequency of co-citation.Results. When analyzing the publications, two clusters of the "drug supply" concept were formed for the time periods indicated above. The comparison of the clusters showed an increase in the activity of the scientific research to expand the structure and content of the subject area of the "drug supply" concept. For the modern cluster, 124 co - cited pairs of lexical units were selected. They were grouped into 9 hierarchy levels according to the strength of relationship between an interval of 10 units and mentioning frequencies of the "drug supply" term. At the final stage, a graphical model of the "drug supply" concept cluster was formed. It was established that the lexical units included from the first to the fifth level, are the cluster nucleus of the "drug supply" concept as the most stable part of the lexical array, which it is advisable to rely on when developing a definition for the concept under study.Conclusion. Thus, the subject field of the "drug supply" concept is characterized by the scientific research, reflecting the socio-economic significance of the objects under study in the field of pharmaceutical activities, and its content is characterized by a high level of pharmaceutical knowledge which describes the most stable elements that make it possible to formulate an adequate definition of the "drug supply" definition.